Кримінальне провадження на підставі угоди про визнання винуватості - Новак, Р. В.; Novak, R. V. (Право і безпека. - 2014. - № 4 (55). - С. 131-137, 2014)
Визначено основні етапи укладання угоди про визнання винуватості, окреслено порядок розгляду угоди про визнання винуватості в суді першої інстанції, вказано суб’єктів, які вправі укладати таку угоду, охарактеризовано правові наслідки укладення угоди про визнання винуватості у кримінальному провадженні. Зроблено висновок, що угода про визнання винуватості створює умови для співпраці підозрюваного чи обвинуваченого з правоохоронним органами і, як наслідок, викриття більшої кількості кримінальних правопорушень, швидкого здійснення досудового розслідування, раціонального розгляду кримінального провадження в суді першої інстанції тощо.

Legal consequences of concluding the agreement are analyzed; the rules of punishment assignment agreed between the suspect or accused and the prosecutor while reaching the agreement are characterized. The objective of the article is to define the main stages of a guilt agreement conclusion, to realize comparative and legal analysis of domestic and international legislation concerning the procedure of guilt agreement’s application. The methodological basis of the article is a set of general and specific methods of research. Structural and logical method was used for the development and characteristics of the seven stages of concluding the guilt agreement. Formal and legal, dialectical methods were used to determine the role of the defense counsel, victim and other participants of the criminal proceedings while concluding the guilt agreement. Comparative and legal method allowed to find out the features of applying the institution of agreements in the Republic of Moldova, Federal Republic of Germany. Based on the statistics of the activity of pretrial investigation agencies in 2013 – 2014 it is noted that the statutory possibility to conclude the agreement between the suspect or accused and the prosecutor has received positive results in the society and has become popular alternative way to solve criminal and legal conflicts. It is pointed out that the institution of guilt agreements creates the conditions for cooperation between the suspect or accused with law enforcement agencies, fast pre-trial investigation, rational consideration of criminal proceedings in the court of the first instance, disburden courts of appeal.

Определены основные этапы заключения соглашения о признании виновности, очерчен порядок рассмотрения соглашения о признании виновности в суде первой инстанции, указаны субъекты, которые вправе заключать такое соглашение, охарактеризованы правовые последствия заключения соглашения о признании виновности в уголовном производстве. Сделан вывод, что соглашение о признании виновности создаёт условия для сотрудничества подозреваемого или обвиняемого с правоохранительными органами и, как следствие, разоблачения большего количества уголовных преступлений, быстрого осуществления досудебного расследования, рационального рассмотрения уголовного производства в суде первой инстанции и т. д.
Criminal proceedings on the basis of guilt agreement
Уголовное производство на основании соглашения о признании виновности
Keywords: угода про визнання винуватості; суд; прокурор; підозрюваний; кримінальне провадження; agreement on the recognition of guilt; court; prosecutor; suspect; criminal proceedings; соглашение о признании виновности; подозреваемый; уголовное производство